NUTRITIONAL IMPROVEMENT OF CHAPATTI USING SOY HULLS - Khan, Muhammad Issa; Anjum, Faqir Muhammad; Akhtar, Saeed (Journal of Research (Science), 2025)
Five treatments of composite flours along with control were prepared by supplementing soy flour in wheat flour @ 1.5, 3, 4.5, 6 and 7.5% to improve nutritional quality of chapattis with respect to minerals (Ca, Mg, Fe, Zn, Mn and Cu) and phytic acid. Composite flours and chapattis were analyzed for their mineral and phytic acid content to assess the changes as a function of baking. Supplementation significantly increased mineral content of flours and this increase was also indicated in chapattis prepared from their respective flours. There was a decrease (20%) in the phytic acid content of the chapatti samples during baking. Sensory evaluation of the chapattis showed that chapattis with 4.5% replacement of wheat flour with soy hulls were accepted by the panel of judges.